Nursing assistance in the care of children with autism: therapies that support the development process - Navarro, Ana Célia Santana; Mafra, LouiseLouise Cristine dos Santos; Botelho, Rayane Martins (JRG Journal of Academic Studies, 2024)
Introduction: According to the American Psychiatric Association (2014), Autism Spectrum Disorder is characterized by stereotypical patterns and difficulty communicating. It is a neurological condition that affects social interaction. The treatment involves several therapies that prioritize development. Nursing plays an important role in individualized care in this scenario. Objective: The objective of this study is to identify the role of nursing in the care of autistic children within a multidisciplinary team and the therapies that assist in the development process. Methodology: This article was conducted in the form of a narrative review based on studies from the last ten years that address the role of nursing and the therapies used in the development process at each stage of life of children with Autism Spectrum Disorder. Result: This study highlights the role of nursing from the initial assessment to the implementation of individualized therapies. Therapies were found for early childhood (0-3 years), preschool (3-6 years) and school (6-12 years). Conclusion: Despite the difficulty in finding new studies that address the topic, the article made it possible to understand the importance of nursing in the care of children with ASD within the multidisciplinary context and partnership with the relevance of the therapies discovered to improve communication, social interaction and behavior.